Kajian Literatur: Jamur Mikoriza Sebagai Mitra Mikroorganisme Yang Meningkatkan Serapan Nutrisi Tanaman - Waruwu, Ardianus Berkat Saleh; Mendrofa, Putri Khide Talenta; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
The current reliance on chemical fertilizers has caused many problems in agricultural practices, such as the decline in soil quality and crop resistance to environmental stress. Farmers are encouraged to use chemical fertilizers, due to the lack of efficiency of nutrient absorption in plants which results in a lack of productivity of agricultural products. This research aims to review in depth the role of Mycorrhizal fungi in increasing the efficiency of nutrient uptake by plants. The research method used is the literature review method to explore more deeply the role of mycorrhizal fungi in increasing the efficiency of plant nutrient uptake. The results stated that mycorrhizal fungi have great potential as microorganism partners in increasing plant nutrient uptake. With its ability to expand the root absorption area, and enhance plant growth, improve soil structure and reduce pollution, mycorrhiza can contribute significantly to agricultural sustainability.